KONTROVERSI HADIS INNA ABῘ WA ABĀKA FĬ AL-NĀR (TELAAH SANAD DAN MATAN HADIS) - Prayitno, Mujahid Agil; Ikmal, Ikmal; Sulfa, Nafilah (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to explain the position of the hadith